2017
DOI: 10.1111/nyas.13505
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence and regulatory approaches of nonbiological complex drug products across the United States, the European Union, and Turkey

Abstract: Regulatory agencies around the world may have different standards and approaches to evaluate and approve drug products and biological products. We describe the U.S. Food and Drug Administration's (FDA) Generic Drug User Fee Act program, as well as their approach to complex products. We discuss regulatory approaches for the development of nonbiological complex drug follow-ons and approval pathways in the United States. We compare FDA policies with other regulatory agencies (i.e., the European Medicines Agency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…While similar results in PT and ES can be explained by similarities between Spanish and Portuguese pharmaceutical markets, in TR, these findings are most likely more influenced by different drug-regulatory measures. 57…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While similar results in PT and ES can be explained by similarities between Spanish and Portuguese pharmaceutical markets, in TR, these findings are most likely more influenced by different drug-regulatory measures. 57…”
Section: Discussionmentioning
confidence: 99%
“…Even if licensing processes in both of the countries are now harmonized with EU legislation, national authorization procedures still dominate. 57 Table 2 shows that national authorization procedures in these countries contribute to lower availability of active substances, and in the case of RS, also to lower availability of PIMs. This is fairly different in TR, where the prevalence of approved PIMs was high, and also the total number of registered medicinal products was the highest (see Table 2), as well as the variability of different approved brand names, strengths, and drug forms of PIMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most frequently administered nanomedicines on the market is iron nanoparticles, which make up 14% of all FDA-approved nanodrugs. These products are iron-carbohydrate colloids/nanoparticles that are administered intravenously (IV) to treat iron deficiency anemia (IDA). , IDA is commonly seen in patients with chronic kidney disease (CKD), which often accompanies type 2 diabetes; in cancer patients, for whom treatment with chemotherapeutic agents leads to anemia; and in some patients with autoimmune disorders. , …”
Section: Introductionmentioning
confidence: 99%
“…There have been no additional generic iron nanoparticle type products approved in the subsequent eight years, despite an interest in approving additional products . In the intervening years, efforts to define how nanomedicines should be regulated have been made both by the FDA in the US and analogous regulatory agencies abroad. ,, Generic nanomedicines in the US are subject to the same regulations as conventional small molecule drugs; however, nanoparticle-based drugs have unique properties. , It has been suggested that new guidance for nanomedicines as a group or specific guidance for specific nanomedicines are needed. ,, For the latter, there is product-specific guidance for SFG that was issued in 2013, in which qualitative (Q1) and quantitative (Q2) formulation sameness, in vivo pharmacokinetic bioequivalence studies, and in vitro characterization including physicochemical properties are recommended. ,, …”
Section: Introductionmentioning
confidence: 99%